2019
DOI: 10.1016/j.jid.2018.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Production of Extracellular Adenosine by CD73+ Dendritic Cells Is Crucial for Induction of Tolerance in Contact Hypersensitivity Reactions

Abstract: Dendritic cells (DCs) express the ecto-5 0-nucleotidase CD73 that generates immunosuppressive adenosine (Ado) by dephosphorylation of extracellular Ado monophosphate and diphosphate. To investigate whether CD73derived Ado has immune-suppressive activity, 2,4-dinitrothiocyanobenzene (DNTB) was applied to skin of wild-type (WT) or CD73-deficient (CD73 e/e) mice, followed by sensitization and challenge with 2,4dinitrofluorobenzene. In this model, we show the induction of tolerance by DNTB against 2,4dinitrofluoro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…In the absence of CD73 DCs fail to cause adenosine accumulation and tolerize against hypersensitivity reactions induced by 2,4-dinitrothiocyanobenzene (DNTB) in vivo. CD73 deficient DCs also fails to induce T cell markers of anergy such as EGR2 and NDRG1 and suppress T cell proliferation in vivo and in vitro [13]. A2AR and A2BR signaling in myeloid cells.…”
Section: Dendritic Cellsmentioning
confidence: 99%
“…In the absence of CD73 DCs fail to cause adenosine accumulation and tolerize against hypersensitivity reactions induced by 2,4-dinitrothiocyanobenzene (DNTB) in vivo. CD73 deficient DCs also fails to induce T cell markers of anergy such as EGR2 and NDRG1 and suppress T cell proliferation in vivo and in vitro [13]. A2AR and A2BR signaling in myeloid cells.…”
Section: Dendritic Cellsmentioning
confidence: 99%
“…Studies have reported that only ~2–10% of freshly isolated human monocytes express CD73 ( 64 ). In mouse BMDCs, CD73 was easier to find in immature BMDCs than in mature BMDCs ( 65 ). M1 macrophages have been reported to exhibit a modest decrease in the expression of both CD39 and CD73, while M2 macrophages express higher levels of both ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…Liu C et al’s study showed that stimulation of adenosine-A2AR axis could inhibit the maturation and proinflammatory function of reoxygenated DCs [ 77 ]. Moreover, Silva-Vilches C and colleagues found that generation of adenosine by CD73 + DCs was a crucial mechanism for the induction of anergic T cells and tolerance [ 78 ]. In vitro , ADA1 induced mDC maturation and ADA1 treatment also promoted the secretion of the IL-6 from mDCs [ 79 ].…”
Section: Adenosine Pathway Regulated the Immune Cells Of Slementioning
confidence: 99%